2019
DOI: 10.1038/s41598-019-56227-y
|View full text |Cite
|
Sign up to set email alerts
|

Extensive recombination challenges the utility of Sugarcane mosaic virus phylogeny and strain typing

Abstract: Sugarcane mosaic virus (SCMV) is distributed worldwide and infects three major crops: sugarcane, maize, and sorghum. The impact of SCMV is increased by its interaction with Maize chlorotic mottle virus which causes the synergistic maize disease maize lethal necrosis. Here, we characterised maize lethal necrosis-infected maize from multiple sites in East Africa, and found that SCMV was present in all thirty samples. This distribution pattern indicates that SCMV is a major partner virus in the East African maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…However, the growing evidence of "divergent" PVY isolates escaping accurate identification using such tests, which were developed with a limited pool of isolates [42], pinpoints the usefulness of complete genome analyses to characterize PVY strain variability [16]. Indeed, the challenges of viral strain identification due to extensive recombination were recently addressed for the sugarcane mosaic virus (SCMV), another member of genus potyvirus, where it was advised to use whole genome phylogenetic analysis for viral strain identification [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the growing evidence of "divergent" PVY isolates escaping accurate identification using such tests, which were developed with a limited pool of isolates [42], pinpoints the usefulness of complete genome analyses to characterize PVY strain variability [16]. Indeed, the challenges of viral strain identification due to extensive recombination were recently addressed for the sugarcane mosaic virus (SCMV), another member of genus potyvirus, where it was advised to use whole genome phylogenetic analysis for viral strain identification [43].…”
Section: Discussionmentioning
confidence: 99%
“…Potyviruses represent the largest and most economically damaging group of known plant RNA viruses [4]. Potyviruses are aphid-borne, infecting both monocotyledonous and eudicotyledonous angiosperms [7].…”
Section: Main Textmentioning
confidence: 99%
“…From the genome information, RT-PCR diagnostics were developed [58]. Whole-genome information revealed that getting reliable tests for SCMV would be tricky due to high genetic diversity and virus recombination [41]. Therefore, the most reliable tests for MLN are anchored on detection of MCMV, which is risky.…”
Section: Case Study 1 Maize Lethal Necrosis Diseasementioning
confidence: 99%